Students’ Perspectives in Writing Narrative Texts Using the Animated Film - Muhammad Dwiyan Aditiya (Ahmad Dahlan Journal of English Studies, 2022)
This article investigated the students’ responses to narrative text through the animated film. The place of this study was one of the public schools in Yogyakarta Province. The subject of this study was eleventh-grade students. This study was implemented in three phases, e.g., the reconnaissance process, cycle one, and cycle two. The stages conducted in this study contained four steps: planning, implementation, observation, and reflection. Moreover, the type of data of this study was qualitative data. The technique of collecting data used in this study was the observation checklists and interview guidance. Furthermore, the technique of analyzing this study's data used descriptive statistics and descriptive analysis. The observation showed that the students’ perception of the students’ interest, attention, activeness, and concentration improved. Besides, the interview result showed that the animated film brought a sense of happiness and a reduced sense of distress among the students during the learning activity. The animated film was also considered a medium to replace conventional teaching methods, e.g., teaching books. The animated film was also a trigger for the students to give their attention during the ongoing class. The animated film was also regarded as an innovation in class activity (including teaching methods, learning ideas, and learning atmosphere) so that the class became alive.